Numerical Investigation of the Anti-infiltration and Anti-Erosion Performance of Composite Layers Mixed With Polyacrylamide and Basalt Fibre for the Protection of Silt Subgrade Slopes - Guo, Shuangfeng; Xu, Peiwen; Zhang, Peng; Wang, Shengnian (Frontiers in Earth Science, 2022)
In view of the failure characteristics of rainfall erosion and imbricate layered sliding of silt subgrade slopes, this paper proposes a slope surface protection technology that is a composite protection layer that combines basalt fibre for reinforcing soil and polyacrylamide for solidifying soil. The anti-infiltration and anti-erosion performances of these proposed composite layers were systematically investigated through the finite element and discrete element numerical simulation methods. Based on the optimum proportions of polyacrylamide and basalt fibre found in a series of mechanical experiments, Geo-studio software was used to simulate numerical tests of rainfall infiltration of the silt subgrade slope, and the variation laws of volumetric water content and pore water pressure at the characteristic points and the selected sections of the slope were discussed. In addition, the PFC2D particle flow program was used to develop numerical tests on the slope erosion process of the composite layers and to analyze the degree of soil erosion during the process. The influences of layer thickness on infiltration and erosion were considered. In conclusion, the results indicate that the composite layers can effectively improve the anti-infiltration and anti-erosion performances of the silt subgrade slope. This highlights that the thickness of composite layers mixed with basalt fibre can satisfy the design parameter requirements for anti-erosion performance.